Relationship of Batak Karo, Batak Toba, And Nias Comparative Historical Linguistic Study - Desy Lampita Rajagukguk; Dwi Widayati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Batak language families such as Karo, Toba, Mandailing, Simalungun, and Angkola have dominant language users, especially Batak Karo and Batak Toba. In addition to the Batak language family, Nias language is also one of the languages ​​whose users are quite a lot in North Sumatra, eventhough it is not the area of ​​origin. Kinship Language is a comparative historical linguistic study. By using the quantitative method the kinship relations of the three languages ​​are calculated lexicostatistically. The indicator used to determine related words is a basic vocabulary called the Swadesh basic vocabulary, which consists of two hundred vocabularies. The first result was obtained, namely the Batak Karo language (BBK) and the Batak Toba language (BBT) have a kinship relationship, where from 200 words there are 121 words that have a kinship relationship, namely 37 identical related words and 84 shifting related words with the same meaning. The level of kinship between the Batak Toba language and the Batak Karo language is fairly high because the percentage is 60.5%. The year of separation occurred in 703 AD. The second is that the Batak Karo language and the Nias language (BN) have a kinship relationship. From 200 words there are 49 words that have kinship relations, namely 13 identical related words and 36 shifted related words with the same meaning. The level of kinship is relatively low because the percentage is 24.5%. The year of separation occurred in 1036 BC. The third is that Batak Toba language and Nias language have a kinship relationship, seen from 200 basic words, there are 50 words that have kinship relationships, namely 12 identical related words and 38 shifted related words with the same meaning. The level of kinship between the Batak Toba language and the Nias language is relatively low because the percentage is 25%. The year of separation occurred in 1022 AD